The Influence Of Facilities And Work Environment On Employee Performance At The Mulak Sub-District Office A Whole Bunch Of Cabbage - Maya Julia; Kasinem Kasinem; M. Pahlan (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to determine the Influence of Facilities and Work Environment on Employee Performance at the Mulak Seframe Sub-district Office, Lahat Regency either partially or simultaneously. This study is a quantitative associative research using the census method in determining the sample. The sample used in this study amounted to 41 people who were used as research respondents. Based on the results of the study, the regression equation Y = 2.032 + 0.309 X1 + 0.635 X2 + e, means that without the variables Facility (X1) and Work Environment (X2), the Employee Performance (Y) is 2.032. The value of the determination coefficient (R2) is 0.752, meaning that the independent variables have a contribution with the dependent variable of 75.2% and the remaining 24.8% is influenced by other factors that were not studied by the author. Based on the results of SPSS processing version 25.0, the Fcal value was obtained of 57.750 while the Ftable value was 3.245 thus 57.750 > 3.245, then Ho was rejected and Ha was accepted, meaning that the variables of Facility (X1) and Work Environment (X2) together have a significant effect on Employee Performance (Y). The Ttable value is 1.685. By comparing the values of Thcal and Ttabel it can be concluded: the Facility variable (X1) with the value of Thcal > Ttable or 2.096 > 1.685 , then Ho is rejected and Ha is accepted. Work Environment (X2) with a Thcal value of > Ttable or 4.444 > 1.685, then the variables of Facilities (X1) and Work Environment (X2) have a partial effect on Employee Performance (Y) at the Mulak Seframe Sub-district Office, Lahat Regency.